2016
DOI: 10.1038/srep18934
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Canonical NF-κB Signaling by a Small Molecule Targeting NEMO-Ubiquitin Interaction

Abstract: The IκB kinase (IKK) complex acts as the gatekeeper of canonical NF-κB signaling, thereby regulating immunity, inflammation and cancer. It consists of the catalytic subunits IKKα and IKKβ and the regulatory subunit NEMO/IKKγ. Here, we show that the ubiquitin binding domain (UBAN) in NEMO is essential for IKK/NF-κB activation in response to TNFα, but not IL-1β stimulation. By screening a natural compound library we identified an anthraquinone derivative that acts as an inhibitor of NEMO-ubiquitin binding (iNUB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 55 publications
3
37
0
Order By: Relevance
“…S11), in particular residues around the hydrophobic patch I44 and the previously mentioned E182 surface. The observed interaction sites are in agreement with observed NMR chemical shifts perturbations reported in Vincendeau et al 23 . The ensemble also provides a possible explanation for the different binding stoichiometry observed in solution (NEMO:Ub2 2:1) and crystalline state (NEMO:Ub2 2:2).…”
Section: The Conformational Entropy Of Long Linear Poly-ubiquitins Mosupporting
confidence: 92%
See 3 more Smart Citations
“…S11), in particular residues around the hydrophobic patch I44 and the previously mentioned E182 surface. The observed interaction sites are in agreement with observed NMR chemical shifts perturbations reported in Vincendeau et al 23 . The ensemble also provides a possible explanation for the different binding stoichiometry observed in solution (NEMO:Ub2 2:1) and crystalline state (NEMO:Ub2 2:2).…”
Section: The Conformational Entropy Of Long Linear Poly-ubiquitins Mosupporting
confidence: 92%
“…In order to study the dynamics and changes of linear poly-ubiquitin dynamics upon binding to cognate proteins, we used simulations and experiments to characterize the interaction of the NEMO UBAN domain (NEMO258-350) to the linear poly-ubiquitins Ub2, Ub3 and Ub4. The NEMO UBAN domain is a dimer in solution 23 . Previous studies have shown two different binding stoichiometries in solution and crystalline state for Ub2: with either two NEMO monomers bound to one Ub2(2:1) or two NEMO monomers bound to two Ub2 (2:2) 23-24 .…”
Section: The Conformational Entropy Of Long Linear Poly-ubiquitins Momentioning
confidence: 99%
See 2 more Smart Citations
“…The interaction of linear ubiquitin chains with NEMO‐UBAN alters the conformation of NEMO , which may have an allosteric effect, regulating IKK kinase activity and downstream signaling. Genetic and pharmacological inhibition of the interaction between NEMO‐UBAN and linear ubiquitin chains preclude the full activation of NF‐κB, revealing an important role for the NEMO‐linear ubiquitin chain interaction in regulating the NF‐κB pathway. Whether NEMO‐UBAN binds to linear ubiquitination formed on NEMO itself, and whether this interaction affects the oligomeric state of the IKK complex, remain unclear.…”
Section: Linear Ubiquitin Chain‐specific Binding Domains and Their Bimentioning
confidence: 99%